Human DAZL, DAZ and BOULE genes modulate primordial germ cell and haploid gamete formation - Kee, Kehkooi (2009)
The leading cause of infertility in men and women is quantitative and qualitative defects in human germ cell (oocyte and sperm) development. Yet, it has not been possible to examine the unique developmental genetics of human germ cell formation and differentiation due to inaccessibility of germ cells during fetal development. Although several studies have shown that germ cells can be differentiated from mouse and human embryonic stem cells, human germ cells differentiated in these studies generally did not develop beyond the earliest stages1-8. Here we used a germ cell reporter to quantitate and isolate primordial germ cells derived from both male and female hESCs. Then, by silencing and overexpressing genes that encode germ cell-specific cytoplasmic RNA-binding proteins (not transcription factors), we modulated human germ cell formation and developmental progression. We observed that human DAZL (Deleted in AZoospermia-Like) functions in primordial germ cell formation, whereas closely-related genes, DAZ and BOULE, promote later stages of meiosis and development of haploid gametes. These results are significant to the generation of gametes for future basic science and potential clinical applications.